1. The problem statement, all variables and given/known data I need to integrate dx/dt=k(a-x)(b-x) and then rearrange to find x 3. The attempt at a solution 1/((a-x)(b-x))dx = k dt Integrating dx using partial fractions: 1/(b-a)×(ln((a-x)/(b-x))=kt+c when t=0 x=0 ∴c=(ln(a/b))/(b-a) then when I rearrange I get: x=(e^((b-a)(kt+c))×(a-b))/((e^((b-a)(kt+c))-1) Then I change the x to y and t to x so that I can graph it, but it doesn't give me the curve that I want, I have attached the graph. I am was assuming that it would give something like the black curve rather than the red one that it gave. Am I doing something wrong?